KEPUASAN KERJA DAN KARAKTERISTIK GURU MATEMATIKA - Della Haya Halimah; Ayu Faradillah (HISTOGRAM: Jurnal Pendidikan Matematika, 2021)
Teacher job satisfaction has a positive effect on effective learning, therefore it is necessary to increase teacher job satisfaction. Teacher job satisfaction should also be a priority in education policy. This study aims to analyze job satisfaction and teacher characteristics in learning mathematics. This study uses qualitative data. Data was collected using questionnaires and interviews. The results of the data obtained were transferred to Ms. Excel is then processed using Winstep software to get high, medium, low levels of teacher job satisfaction. For research subjects,  there are 94 mathematics teachers in Jakarta and outside Jakarta. The results showed that 3 male teachers and 14 male teachers had a high level of job satisfaction. 17 male teachers and 38 female teachers had a moderate level of job satisfaction, 5 male teachers and 17 female teachers had a low level of job satisfaction. Then the researcher took 1 respondent from each area of Jakarta and outside Jakarta to be interviewed.According to the Wright Maps results, female mathematics teachers have the highest teacher job satisfaction, namely 14 people. According to the results of interviews, female teachers are satisfied to be teachers because of school infrastructure, salaries, student characteristics, increasing knowledge, getting good colleagues, and good principals.